QoS Prediction forWeb Services Based on Similarity-Aware Slope One Collaborative Filtering - Mao, Chengying; Chen, Jifu (Informatica)
QoS Prediction forWeb Services Based on Similarity-Aware Slope One Collaborative Filtering